Serum Level of Zinc in Children with Febrile Seizures - Ambalavanan, Ashwini; Sugumar, Ashwathi; Elangovan, Elakkiyaa; Chaudhary, Devanand Gulab (Journal of Neonatal Surgery, 2025)
Objective: Febrile seizure is the most common pediatric population, usually occurring between six months to five years of age, which typically manifests during febrile illness. While the exact pathophysiology remains unclear, several factors are implicated, including genetic predisposition and variations in electrolyte levels such as zinc. In this study, we evaluated zinc level in children with the first FS attack and febrile children without seizure. Materials and Methodology: This is a prospective study conducted among 30 patients with febrile seizure and 30 patient who are febrile without seizure. The children are within the age group of 6 months to 5 years. Serum zinc levels were measured by atomic absorption spectroscopy in these group. Conclusion: Based on the present results, serum zinc level was lower in children with febrile seizures. However, further research is needed to examine the efficacy of zinc supplementation in prevention of febrile seizure